Removal of high concentration phenol from aqueous solutions by electrochemical technique - Shaimaa T. Alnasrawy; Ghayda Y. Alkindi; Talib M. Albayati (Engineering and Technology Journal, 2021)
In this study, the ability of the electrochemical process to remove aqueous high concentration phenol using an electrochemical cell with aluminum anode and cathode was examined. The removal rate of phenol was monitored using different parameters phenol concentration, pH, electrolysis time, current density, and electrode distance. Obtained results indicated that the low removal rates of phenol were observed at both low and high pH. However, the removal rate of phenol increased with an increase in the current density, each electrochemical process conditions need a certain electrodes distance. removal rate of phenol decreased with the increase in the initial phenol concentration. The maximum removal rate of phenol obtained from this study was 82%.